2018
DOI: 10.1007/s10158-018-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional organization of the brain and distribution of serotonin in the brain and ovary, and its effects on ovarian steroidogenesis in the giant freshwater prawn, Macrobrachium rosenbergii

Abstract: The giant freshwater prawn, Macrobrachium rosenbergii, is an economically important crustacean species which has also been extensively used as a model in neuroscience research. The crustacean central nervous system is a highly complex structure, especially the brain. However, little information is available on the brain structure, especially the three-dimensional organization. In this study, we demonstrated the three-dimensional structure and histology of the brain of M. rosenbergii together with the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Meeratana et al ( 46 ) reported that serotonin-primed thoracic ganglion medium accelerated ovarian development in M. rosenbergii , indicating an indirect effect of serotonin on reproduction. The localization of serotonin-immunoreactive cells in the X-organ neurons and fibers innervating the sinus gland tissue and in other parts of the central nervous system of various decapod crustaceans ( 57 , 63 ) support the suggested regulatory role of serotonin in the synthesis and release of other neurohormones from the XO/SG complex such as CHH ( 64 , 65 ) and probably other neuropeptides of the CHH-family ( 56 ). However, the presence of serotonin immunoreactivity was also observed in crustacean gonads ( 46 , 56 , 57 , 63 ) and its stimulatory effects on gonad maturation confirmed, thereby further advocating an autocrine/paracrine mode of receptor-mediated action for serotonin in the control of crustacean oocyte maturation.…”
Section: Serotoninmentioning
confidence: 53%
See 2 more Smart Citations
“…Meeratana et al ( 46 ) reported that serotonin-primed thoracic ganglion medium accelerated ovarian development in M. rosenbergii , indicating an indirect effect of serotonin on reproduction. The localization of serotonin-immunoreactive cells in the X-organ neurons and fibers innervating the sinus gland tissue and in other parts of the central nervous system of various decapod crustaceans ( 57 , 63 ) support the suggested regulatory role of serotonin in the synthesis and release of other neurohormones from the XO/SG complex such as CHH ( 64 , 65 ) and probably other neuropeptides of the CHH-family ( 56 ). However, the presence of serotonin immunoreactivity was also observed in crustacean gonads ( 46 , 56 , 57 , 63 ) and its stimulatory effects on gonad maturation confirmed, thereby further advocating an autocrine/paracrine mode of receptor-mediated action for serotonin in the control of crustacean oocyte maturation.…”
Section: Serotoninmentioning
confidence: 53%
“…Increasing levels of serotonin were observed in the ovaries of P. monodon ( 50 ), L. vannamei ( 56 ), and M. rosenbergii ( 52 ) during the early ovarian maturation stages, reaching maximum levels at the mature ovarian stages. In support of this observation, Soonthornsumrith et al ( 57 ) also suggested that serotonin in both the central nervous system and ovary act in harmony to control oocyte maturation. A combination of spiperone (a dopamine antagonist) and serotonin was shown to induce ovarian maturation in M. rosenbergii ( 58 ) together with enhanced spawning in L. vannamei and Litopenaeus stylirostris ( 59 ) compared with the injection of serotonin alone.…”
Section: Serotoninmentioning
confidence: 84%
See 1 more Smart Citation
“…Taken together, it is concluded that the activation of OR10H2 through serotonin promotes successful fertilization by preventing cumulus cell senescence and improving oocyte survival. Furthermore, it is likely that the serotonin-mediated OR10H2 stimulation and the subsequent OMP activation in competent oocytes trigger an OR-dependent signal transduction cascade between the nervous and endocrine systems to help ovarian steroid secretion and to enhance oocyte quality (Kang et al, 2015;Soonthornsumrith et al, 2018). Given the previous findings, serotonin could also regulate progesterone secretion by granulosa cells (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…bind to the secreted serotonin and maintain the oocyte development and fertilization potential through the activation of AC3 and cAMP production in cumulus cells (Doty and Kamath, 2014;Soonthornsumrith et al, 2018). Giacomo et al have shown that cAMP elevation prevents cumulus cell apoptosis and allows them to preserve oocyte fertilizability through exerting protective effects on oocyte (Di Giacomo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%